The Cognitive consequences of envy attention, memory, and self-regulatory depletion. [article]. - Hill, Sarah E.
In a series of 4 experiments, we provide evidence that-in addition to having an effective component envy may also have important consequences for cognitive processing. Our first experiment (N=69)demonstrated that individuals primed with envy better attended to and more accurately recalled information about fictitious peers than did a control group. Studies 2(N=187) and 3(N=65) conceptually replicated these results, demonstrating that envy elicited by targets predicts attention and later memory for information about them. We demonstrate that these effects cannot be accounted for by admiration or changes in negative affect or arousal elicited by the targets. Study 4(N=152)provides evidence that greater memory for envied-but not neutral-targets leads to diminished perseverance on a difficult anagram task. Findings demonstrate that envy may play an important role in attention and memory systems and deplete limited self-regulatory resources available for acts of violation.-(From the authors)